A Study of Chudka, Kauda, Ghatu, and Maruni as Representatives of Indigenous Literature - Gurung, Raj Kumar; Rai, Ram Prasad (International Journal of Language and Literary Studies, 2024)
This paper explores select representative Indigenous literature of Nepal with a full retrospect of underlying meanings by analyzing the symbols and images of Chudka, Kauda, Gh?t?u and Maruni which represent multicultural indigenous imageries. Ethnic groups such as Gurung and Magar commonly practice these indigenous cultural activities in the mid-western parts of Nepal. In particular, the research concerns these folk dances’ symbolic interpretation and kinesthetic impacts. These traditional folk dances are based on myths, shamanism, and spirituality. They represent the entire ethno-dance performance of the country. There are only a few researchers in this field. These dances are the representatives of folklore, folk literature, and the archives, which contribute to mainstream literature. The universal implication of these dance performances and Indonesian Barong dance is of the same rate. These folk dances play a vital role in fostering the whole literary domain. The research questions are: Why are such ethno-dance performances which represent indigenous literature seemingly neglected? Do the symbolic interpretations of cultural dance performances enhance indigenous literature? This research abstract aims to investigate the factors contributing to the demise of these indigenous dance performances. Through document analysis and survey methods, this study examines the reasons for the decline and over-infiltration of European cultures like baby shower and cake cultures that have led to the dwindling presence of indigenous literature. Furthermore, though anthropological and sociological research was done to look at human evolution, these dance performances have not been interpreted from semiotic and performance perspectives. The study employs Schechner’s performance theory, Chandler’s semiotic theory, and Neupane’s folk drama theory. As a qualitative research paper, we have used textual analysis as a tool to conclude the discussion.